2019
DOI: 10.1088/1361-6560/ab2f44
|View full text |Cite
|
Sign up to set email alerts
|

Impact of image preprocessing on the scanner dependence of multi-parametric MRI radiomic features and covariate shift in multi-institutional glioblastoma datasets

Abstract: Recent advances in radiomics have enhanced the value of medical imaging in various aspects of clinical practice, but a crucial component that remains to be investigated further is the robustness of quantitative features to imaging variations and across multiple institutions. In the case of MRI, signal intensity values vary according to the acquisition parameters used, yet no consensus exists on which preprocessing techniques are favorable in reducing scanner-dependent variability of image-based features. Hence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 48 publications
4
71
0
1
Order By: Relevance
“…Variation in the brain MRI intensity distribution because of the difference in inter‐ and intra‐scanners sensitivity and acquisition parameters leads to complicated in image quantitative analysis, even for the same protocol, tissue, patient, and scanner. Consequently, intensity normalization is essential for providing the same tissue intensity scale in brain MR images across all observations to facilitate radiomics analysis and accurate quantitative comparison between MRI volumes as is expressed by Eq. (), gRandgI are reference image and the original image intensity respectively, LR and HR are respectively the low and high reference image intensity range.gR=Q||gIfalse∫lRhRHg,I)(qdq…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation in the brain MRI intensity distribution because of the difference in inter‐ and intra‐scanners sensitivity and acquisition parameters leads to complicated in image quantitative analysis, even for the same protocol, tissue, patient, and scanner. Consequently, intensity normalization is essential for providing the same tissue intensity scale in brain MR images across all observations to facilitate radiomics analysis and accurate quantitative comparison between MRI volumes as is expressed by Eq. (), gRandgI are reference image and the original image intensity respectively, LR and HR are respectively the low and high reference image intensity range.gR=Q||gIfalse∫lRhRHg,I)(qdq…”
Section: Methodsmentioning
confidence: 99%
“…Given that MRI undergoes of various inherent acquisition artifacts and noises such as lack of standard intensity for inter‐ and intra‐scanner variability even for the same protocol, body region, and patient; intensity non‐uniformity as a result of reduced radio frequency, coil uniformity, nonlinear fields, gradient field, magnetic field, and etc. ; image preprocessing method suchlike intensity normalization, bias field correction, and noise smoothing can facilitate quantitative MRI analysis and make the radiomics results more repeatable and comparable . Currently, many attentions of the GBM mMRI‐based radiomics studies were drowned to prognosis and prediction model, while they have not used a pre‐specific image preprocessing pipeline.…”
Section: Introductionmentioning
confidence: 99%
“…Even if several studies have shown variabilities in texture analysis depending on MRI acquisition parameters and the grey-level discretization step, none of them has assessed the combined impact of intensity normalization and grey-level discretization pre-processing methods on radiomics feature values in MRI [36][37][38][39][40] .…”
mentioning
confidence: 99%
“…The need for some preprocessing steps before extracting MRI radiomic features has been very recently acknowledged for other tumor types (41,42). Although there is no consensus on the preprocessing methods that should be used, two main pitfalls that are specific to MRI have been identified.…”
Section: Discussionmentioning
confidence: 99%